Simultaneous Spray Drying for Combination Dry Powder Inhaler Formulations - Kimberly B. Shepard; Amanda M. Pluntze; David T. Vodak (Pharmaceutics, 2022)
Spray drying is a particle engineering technique used to manufacture respirable pharmaceutical powders that are suitable for delivery to the deep lung. It is amenable to processing both small molecules and biologic actives, including proteins. In this work, a simultaneous spray-drying process, termed simul-spray, is described; the process involves two different active pharmaceutical ingredient (API) solutions that are simultaneously atomized through separate nozzles into a single-spray dryer. Collected by a single cyclone, simul-spray produces a uniform mixture of two different active particles in a single-unit operation. While combination therapies for dry powder inhalers containing milled small molecule API are commercially approved, limited options exist for preparing combination treatments that contain both small molecule APIs and biotherapeutic molecules. Simul-spray drying is also ideal for actives which cannot withstand a milling-based particle engineering process, or which require a high dose that is incompatible with a carrier-based formulation. Three combination case studies are demonstrated here, in which bevacizumab is paired with erlotinib, cisplatin, or paclitaxel in a dry powder inhaler formulation. These model systems were chosen for their potential relevance to the local treatment of lung cancer. The resulting formulations preserved the biologic activity of the antibody, achieved target drug concentration, and had aerosol properties suitable for pulmonary delivery.